MEMBANGUN KEMANDIRIAN SISWA DENGAN PEMBELAJARAN PRODUK KREATIF DI SMK NEGERI 1 CIPEUNDEUY - Setiawan, Devi Siylvia; Ansori, Ansori (Perspektif Pendidikan dan Keguruan, 2025)
This research was conducted using mixed research methods (mix-method). Researchers used mixed research methods to obtain data in both quantitative and qualitative forms. Sampling in this study used the probability sampling method with multi-stage random sampling. A sample of 94 students was selected from class XII Mechanical Engineering 1, 2, and 3. The data in this study were obtained using a quantitative assessment questionnaire regarding the implementation of creative product learning, student independence attitudes, and qualitative interview guidelines. Based on the results of the statistical tests previously described, it is known that there is a significant relationship between the implementation of creative product learning and the independence of students at SMK Negeri 1 Cipeundeuy with a significance value of 0.000. Implementing creative product learning affects students' independence attitudes by up to 75.9%. And by 34.1% the attitude of independence of students is influenced by other things outside the implementation of creative product learning. The material provided during the lesson is in the form of learning about entrepreneurial skills, entrepreneurial characteristics, creative and commercial products as well as opportunities for creativity and innovation. Students are also given practice in making creative products. In its implementation, students were directed to make cutlery with a ring/fit wrench design as one of the product innovations related to the focus on competence in mechanical engineering skills. The presentation of the material carried out in the classroom by the supporting teacher is given using PowerPoint accompanied by an oral explanation. Constraints experienced by adjustments to a more dynamic and interactive learning process. Supporting teachers also experience problems in the form of difficulties in the process of adjustment and development of the learning process.